2016
DOI: 10.1175/jcli-d-15-0358.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Impacts of Fixing the Southern Ocean Shortwave Radiation Bias in the Community Earth System Model (CESM)

Abstract: A large, long-standing, and pervasive climate model bias is excessive absorbed shortwave radiation (ASR) over the midlatitude oceans, especially the Southern Ocean. This study investigates both the underlying mechanisms for and climate impacts of this bias within the Community Earth System Model, version 1, with the Community Atmosphere Model, version 5 [CESM1(CAM5)]. Excessive Southern Ocean ASR in CESM1(CAM5) results in part because low-level clouds contain insufficient amounts of supercooled liquid. In a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
362
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(389 citation statements)
references
References 46 publications
25
362
2
Order By: Relevance
“…As discussed in Sects. 3 and 4, the results of this study bear remarkable similarity to those of Kay et al (2016), where cloud properties were adjusted, lending further support to this idealised approach. Zonally uniform perturbations to direct and diffuse ocean albedo are applied to counterbalance global annual mean biases in TOA albedo when compared to CERES observations, as further discussed in Sect.…”
Section: Hadgem2-es Climate Modelsupporting
confidence: 74%
See 3 more Smart Citations
“…As discussed in Sects. 3 and 4, the results of this study bear remarkable similarity to those of Kay et al (2016), where cloud properties were adjusted, lending further support to this idealised approach. Zonally uniform perturbations to direct and diffuse ocean albedo are applied to counterbalance global annual mean biases in TOA albedo when compared to CERES observations, as further discussed in Sect.…”
Section: Hadgem2-es Climate Modelsupporting
confidence: 74%
“…The conclusions of the work were not affected by the longer integration period and the circulation changes analysed here are observed within the first few years of the simulations (not shown). Kay et al (2016) found a similar, fast response in their simulations with no material change in the model response after 200 years of simulation time. Given the timescale on which the Atlantic meridional overturning circulation has been observed to adjust to perturbations in other studies using HadGEM2-ES (Menary et al 2013;Menary and Scaife 2014), 100 years is more than sufficient to confirm the full dynamical response of the model to forcing has been achieved in the first two decades.…”
Section: Experimental Designmentioning
confidence: 70%
See 2 more Smart Citations
“…0.2 W m −2 ), which requires an ITCZ shift towards the NH in order to induce an anomalous cross-equatorial atmospheric heat transport towards the SH (Kang et al, 2008(Kang et al, , 2009). It should be noted, however, that the use of a slab ocean model precludes changes in cross-equatorial ocean heat transport, which may exaggerate the ITCZ shift (Kay et al, 2016).…”
Section: Temperature and Precipitationmentioning
confidence: 99%